PENGEMBANGAN E-BOOK INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA SISWA KELAS V DI UPT SPF SD INPRES PARANG - Halisah, Nur; Suryani Sahabuddin, Erma; Rizah Putrawan, Muh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop an interactive e-book to improve the critical thinking skills of fifth-grade students at UPT SPF SD Inpres Parang. The background of this research is the limited availability of digital and interactive teaching materials and the low level of students’ critical thinking skills in the topic of environmental problems threatening life. This research employed a Research and Development (R&D) approach adapted from the Alley & Trollic development model, which consists of three main stages: planning, design, and development. The research subjects were 20 fifth-grade students of UPT SPF SD Inpres Parang. The research instruments included expert validation sheets for content and media, teacher response questionnaires, student response questionnaires, and practicality questionnaires. The results of the study indicate that: (1) the development of the interactive e-book was conducted through systematic steps based on the Alley & Trollic model; (2) the product met the “very valid” criteria with a validity percentage of 89.77%; and (3) the practicality of the interactive e-book reached 68.65% and was categorized as “practical.” Based on the results and discussion, it can be concluded that the interactive e-book meets the feasibility criteria and can be used in the learning process.